Studi Pendapatan Pola Tanam Monokultur (Kakao) ke Tumpang Sari (Jagung dan Bayam) di Binuang - Pagala, Muhamad Arman Yamin; Nurdiyah, Nurdiyah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Cocoa is an export commodity that is widely cultivated by farmers in Polewali Mandar, during the Covid-19 pandemic cocoa distribution patterns were hampered which affected cocoa production and prices decreased. It became a factor that farmers switched to intercropping corn and spinach. The purpose of the study was to look at the income and efficiency of intercropping and monoculture farming patterns. Methods: Determination of location is done purposively, the number of respondents who do farming patterns or switch from cocoa to corn and spinach in Binuang Subdistrict, which was sampled as many as 36 farmers. Data collection techniques, direct observation, interviews and distribution of research questionnaires. Results: Data analysis used is income analysis and R / C ratio, obtained cocoa commodity income during the pandemic Rp. 4,550,933, - per one harvest season every 3-4 months, when farmers switch to intercropping corn commodity Rp. 11,880,000, -. per one season every three months, with value added commodity intercropping spinach Rp. 671,810, - one harvest season every 4-6 weeks. With R/C ratio values for cocoa 1.4, corn 1.9 and spinach 3.2. Conclusions: (1) There was an increase in income when farmers changed the intercropping crop pattern of Rp. 8,000,877 per / ha from monoculture cropping patterns, (2) The R / C ratio value increased by 0.5 for corn crops, and the R / C ratio value of spinach crops by 1.8, indicating that farmers are more feasible when switching to intercropping cropping patterns in the C-19 pandemic transition.